INFLUENCE OF THE BUILDING GEOMETRY ON ENERGY EFFICIENCY OF TIMBER-GLASS BUILDINGS FOR DIFFERENT CLIMATIC REGIONS - Premrov, Miroslav; Žigart, Maja; Žegarac Leskovar, Vesna (Journal of Applied Engineering Science, 2017)
The presented study is focused into examination of the building shape influence on the annual energy need for heating and cooling by taking into account climate data for six European cities located in different climatic regions. The research is performed on timber-glass box-house models parametrically varying building aspect ratio (L/W) and number of storeys (single- and two-storey), while the glazing - to - wall area ratio for southern façade is kept constant for all treated models (AGAW=35%). The influence of the mentioned parameters on the annual energy need is thoroughly analysed and leads to completely different conclusions drawn for cold and warm climate conditions. According to the presented results the recommendation for cold climate conditions is to design two-storey houses rather than single-storey ones. Additionally, the increasing aspect ratio shows a positive influence on the energy need reduction. In the case of warm climate conditions the findings are almost opposite to those for cold climates. The total energy need consist predominantly of data for cooling, whereby the energy need increases with the increasing aspect ratio. On behalf of specifics related to warm climate a further study was conducted for Athens with an additional examination of the building components with higher thermal transmittance (U). The results of the research for Athens show that designers are practically free to choose between single-storey or two-storey buildings with no significant impact on the building energy behaviour. The main output of the current study is to offer designers general information on energy-efficient design parameters for single-family timber-glass buildings under influence of different European climatic conditions.
Keywords: climate impacts; timber-glass buildings; energy demand; aspect ratio